A god loocking for identity: Dionysus in Frogs (Minerva, 2019)
In the Frogs, Aristophanes gives to the god of theater the initiative of a trip, during which Dionysus faces a permanent problem of identity: who is this Dionysus looking for the power that a poet's resurrection represents? The question about Dionysus’ identity doesn’t find an answer within the play; it also puts under discussion the ambiguity of the god and his cult. The ritual allows changes on normal life: sexual order and social hierarchy may be subverted as part of a festival, where subversion and questioning are a priority.
Keywords: cult of Dionysus; katabasis; travel